Being Muslim and working for peace : ambivalence and ambiguity in Gujarat - Susewind, Raphael, 1984-; Sage eBooks (Los Angeles : SAGE, 2013)
This study explores various ways in which religious beliefs, ritual practices and dynamics of belonging impact on the politics of Muslim peace activists in Gujarat, and traces how their activism in turn transforms their sense of being. It challenges popular notions about Muslims in India and questions ill-conceived research designs in the sociology of religion.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Muslims -- Political activity -- India -- Gujarat; Peace-building -- India -- Gujarat -- Citizen participation; Conflict management -- India -- Gujarat; Gujarat (India) -- Politics and government -- 21st century; Peace-building -- Religious aspects -- Islam; Electronic books